Does a long reference list guarantee more citations? Analysis of Malaysian highly cited and review papers - Ale Ebrahim, Nader; Ebrahimian, H.; Mousavi, Maryam; Tahriri, Farzad (Inovatus Services Ltd., 2015)
Earlier publications have shown that the number of references as well as the number of received citations are field-dependent. Consequently, a long reference list may lead to more citations. The purpose of this article is to study the concrete relationship between number of references and citation counts. This article tries to find an answer for the concrete case of Malaysian highly cited papers and Malaysian review papers. Malaysian paper is a paper with at least one Malaysian affiliation. A total of 2466 papers consisting of two sets, namely 1966 review papers and 500 highly-cited articles, are studied. The statistical analysis shows that an increase in the number of references leads to a slight increase in the number of citations. Yet, this increase is not statistically significant. Therefore, a researcher should not try to increase the number of received citations by artificially increasing the number of references.